Manure application decreases soil organic carbon priming by increasing mineral protection and nitrogen availability - Yalin Li; Lei Wu; Lingyun Tang; Fengling Ren; Xihe Wang; Ping Zhu; Nan Sun; Minggang Xu (Geoderma, 2023)
Rational chemical fertilizer application, especially combined with manure or straw amendment, serves as a key strategy for facilitating soil organic carbon (SOC) sequestration and soil fertility improvement. However, the effects of fertilization managements on the SOC priming induced by straw return remains unclear. Here, a microcosm was conducted to clarify the mechanisms of 13C-labeled maize straw addition effects on priming effect (PE) in two 29-year fertilized soils (Urumqi, UQ; Gongzhuling, GZL) subjected to four fertilization regimes (no fertilizer, CK; chemical fertilizers, NPK; combined application of NPK with straw, NPKS; combined application of NPK with manure, NPKM). Results showed that straw addition strongly increased native SOC decomposition by 15–44%, inducing positive PEs across sites and fertilization treatments. Compared to CK treatment, the NPK and NPKS treatments significantly increased PE by 26% and 98%, respectively, in the UQ soil, but had little effect on the PE in the GZL soil. The NPKM treatment strongly decreased PE by 51–55%, mainly due to the increased proportion of mineral-associated organic carbon (MAOC) and N availability, and decreased fungal abundances, as compared to the CK treatment in UQ and GZL soils. The PE intensities were significantly lower in GZL soil (5.1–11.7 mg CO2-C/g SOC) relative to UQ soil (13.7–54.8 mg CO2-C/g SOC), primarily due to the higher MAOC/SOC ratio and N availability in the former across fertilization regimes. Overall, manure application has the potential to mitigate soil C loss via priming, mainly resulting from enhanced SOC stabilization via mineral protection and increased N availability, thus facilitating SOC sequestration in agroecosystems.